Analysis of the Antigenic and Prophylactic Properties of the Leishmania Translation Initiation Factors eIF2 and eIF2B in Natural and Experimental Leishmaniasis - Garde, Esther; Ramírez, Laura; Corvo, Laura; Solana, José C.; Martín, M. Elena; González, Víctor M.; Gómez-Nieto, Carlos; Barral, Aldina; Barral-Netto, Manoel; Requena, José M.; Iborra, Salvador; Soto, Manuel (Frontiers in Cellular and Infection Microbiology, 2018)
Different members of intracellular protein families are recognized by the immune system of the vertebrate host infected by parasites of the genus Leishmania. Here, we have analyzed the antigenic and immunogenic properties of the Leishmania eIF2 and eIF2B translation initiation factors. An in silico search in Leishmania infantum sequence databases allowed the identification of the genes encoding the α, β and γ subunits and the α, β and δ subunits of the putative Leishmania orthologues of the eukaryotic initiation factors F2 (LieIF2) or F2B (LieIF2B), respectively. The antigenicity of these factors was analyzed by ELISA using recombinant versions of the different subunits. Antibodies against the different LieIF2 and LieIF2B subunits were found in the sera from human and canine visceral leishmaniasis patients, and also in the sera from hamsters experimentally infected with L. infantum. In L. infantum (BALB/c) and Leishmania major (BALB/c or C57BL/6) challenged mice, a moderate humoral response against these protein factors was detected. Remarkably, these proteins elicited an IL-10 production by splenocytes derived from infected mice independently of the Leishmania species employed for experimental challenge. When DNA vaccines based on the expression of the LieIF2 or LieIF2B subunit encoding genes were administered in mice, an antigen-specific secretion of IFN-γ and IL-10 cytokines was observed. Furthermore, a partial protection against murine CL development due to L. major infection was generated in the vaccinated mice. Also, in this work we show that the LieIF2α subunit and the LieIF2Bβ and δ subunits have the capacity to stimulate IL-10 secretion by spleen cells from naïve mice. B-lymphocytes were identified as the major producers of this anti-inflammatory cytokine. Taking into account the data found in this study, it may be hypothesized that these proteins act as virulence factors implicated in the induction of humoral responses as well as in the production of the down-regulatory IL-10 cytokine, favoring a pathological outcome. Therefore, these proteins might be considered markers of disease.